Bio-Receptors Functionalized Nanoparticles: A Resourceful Sensing and Colorimetric Detection Tool for Pathogenic Bacteria and Microbial Biomolecules - Daramola, Oluwafemi B.; Omole, Richard K.; Akinwale, Ifeoluwa V.; Otuyelu, Frank O.; Akinsanola, Bolanle A.; Fadare, Taiwo O.; George, Reama C.; Torimiro, Nkem (Frontiers in Nanotechnology, 2022)
Pathogenic bacteria and several biomolecules produced by cells and living organisms are common biological components posing a harmful threat to global health. Several studies have devised methods for the detection of varying pathogenic bacteria and biomolecules in different settings such as food, water, soil, among others. Some of the detection studies highlighting target pathogenic bacteria and biomolecules, mechanisms of detection, colorimetric outputs, and detection limits have been summarized in this review. In the last two decades, studies have harnessed various nanotechnology-based methods for the detection of pathogenic bacteria and biomolecules with much attention on functionalization techniques. This review considers the detection mechanisms, colorimetric prowess of bio-receptors and compares the reported detection efficiency for some bio-receptor functionalized nanoparticles. Some studies reported visual, rapid, and high-intensity colorimetric detection of pathogenic bacteria and biomolecules at a very low concentration of the analyte. Other studies reported slight colorimetric detection only with a large concentration of an analyte. The effectiveness of bio-receptor functionalized nanoparticles as detection component varies depending on their selectivity, specificity, and the binding interaction exhibited by nanoparticles, bio-receptor, and analytes to form a bio-sensing complex. It is however important to note that the colorimetric properties of some bio-receptor functionalized nanoparticles have shown strong and brilliant potential for real-time and visual-aided diagnostic results, not only to assess food and water quality but also for environmental monitoring of pathogenic bacteria and a wide array of biomolecules.